Practice of Financial Management of the Social Sector in Treasury Implementation of the Budget - Касимова Гуляр Ахматовна (European Science Publishing, 2024)
The article examines the planning of state budget revenues and expenses , payment of expenses, preparation of financial reports on budget execution, and financial control tasks of the treasury bodies . Cash execution of the state budget, the mechanism of payment of social sector expenses in the treasury system, and the procedure for introducing the "electronic document circulation" system between budget organizations and the treasury were studied. In the Republic of Uzbekistan, the implementation of successful methods and technologies of the treasury bodies in the payment operations of budget organizations belonging to the social sphere, the operation of the Unified treasury account, the registration of contracts, the effective management of cash flows in the treasury accounts, etc.
Keywords: State budget cash flow, social sector, healthcare system, education, treasury system, budget obligations, payment.